Analisis Kondisi Sosial Ekonomi Masyarakat Daerah Transmigran - Abdulrahim Maruwae; Ardiansyah Ardiansyah (Universitas Negeri Gorontalo, 2020)
This study intends to describe how the socioeconomic conditions of the transmigrant area community. This research uses descriptive qualitative method by using Milles and Huberman analysis design. The research findings show there are social interactions that are established within the community within the framework of harmony and tolerance that is continuously maintained. The values of local wisdom continue to be preserved along with the close social relations of the community. The level of education is still relatively low, with 66% of the population only graduating from junior high school, elementary school or not even attending school, but the population structure shows that 73% of the population is at productive age. The majority of the people's livelihoods are farmers, who manage their land with a variety of commodities including coconut, sugar cane, crops, fruits, and vegetables. The income earned by the community is, on average, sufficient to meet their daily needs. It can be concluded that the socioeconomic conditions of the Banuroja transmigrant community, both transmigrant, local and mixed communities show variations in the prestige or level of achievement of several indicators of socioeconomic conditions.